Dietary Glycotoxins Impair Hepatic Lipidemic Profile in Diet-Induced Obese Rats Causing Hepatic Oxidative Stress and Insulin Resistance. (25th June 2019) - Neves, C.; Rodrigues, T.; Sereno, J.; Simões, C.; Castelhano, J.; Gonçalves, J.; Bento, G.; Gonçalves, S.; Seiça, R.; Domingues, M. R.; Castelo-Branco, M.; Matafome, P.
Abstract : Nonalcoholic fatty liver disease (NAFLD) is caused by excessive liver lipid accumulation, but insulin resistance is specifically associated with impaired lipid saturation, oxidation, and storage (esterification), besides increased de novo lipogenesis. We hypothesized that dietary glycotoxins could impair hepatic lipid metabolism in obesity contributing to lipotoxicity-driven insulin resistance and thus to the onset of nonalcoholic steatohepatitis (NASH). In diet-induced obese rats with methylglyoxal-induced glycation, magnetic resonance spectroscopy, mass spectrometry, and gas chromatography were used to assess liver composition in fatty acyl chains and phospholipids. High-fat diet-induced obesity increased liver lipid fraction and suppressed de novo lipogenesis but did not change fatty acid esterification and saturation or insulin sensitivity. Despite a similar increase in total lipid fraction when supplementing the high-fat diet with dietary glycotoxins, impairment in the suppression of de novo lipogenesis and decreased fatty acid unsaturation and esterification were observed. Moreover, glycotoxins also decreased polyunsaturated cardiolipins and caused oxidative stress, portal inflammation, and insulin resistance in high-fat diet-induced obese rats. Dietary glycated products do not change total lipid levels in the liver of obese rats but dramatically modify the lipidemic profile, leading to oxidative stress, hepatic lipotoxicity, and insulin resistance in obesity and thus contribute to the onset of NASH.